1991
DOI: 10.1111/j.1471-4159.1991.tb02073.x
|View full text |Cite
|
Sign up to set email alerts
|

Phorbol Myristate Acetate and 8‐Bromo‐Cyclic AMP‐Induced Phosphorylation of Glial Fibrillary Acidic Protein and Vimentin in Astrocytes: Comparison of Phosphorylation Sites

Abstract: Both the protein kinase C (PK-C) activator, phorbol 12-myristate 13-acetate (PMA), and the cyclic AMP-dependent protein kinase (PK-A) activator, 8-bromo-cyclic AMP (8-BR), have been shown to increase 32P incorporation into glial fibrillary acidic protein (GFAP) and vimentin in cultured astrocytes. Also, treatment of astrocytes with PMA or 8-BR results in the morphological transformation of flat, polygonal-shaped cells into stellate, process-bearing cells, suggesting the possibility that signals mediated by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

1992
1992
2001
2001

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 22 publications
(14 reference statements)
1
21
0
Order By: Relevance
“…To determine the mechanism underlying the glutamate inhibition of glial stellation, we examined the effect of glutamate on CAMP formation. Our data indicated that the effect of glutamate was not a result of CAMP regulation since 1) glutamate only inhibited a small fraction of ISO-induced CAMP formation compared to NE and 2) glutamate also blocked the stellation induced by PMA which activates protein kinase C rather than CAMP-dependent protein kinase (Harrison and Mobley, 1991 ).…”
Section: Mechanism Of the Glutamate Inhibition Of Glial Stellationmentioning
confidence: 70%
“…To determine the mechanism underlying the glutamate inhibition of glial stellation, we examined the effect of glutamate on CAMP formation. Our data indicated that the effect of glutamate was not a result of CAMP regulation since 1) glutamate only inhibited a small fraction of ISO-induced CAMP formation compared to NE and 2) glutamate also blocked the stellation induced by PMA which activates protein kinase C rather than CAMP-dependent protein kinase (Harrison and Mobley, 1991 ).…”
Section: Mechanism Of the Glutamate Inhibition Of Glial Stellationmentioning
confidence: 70%
“…The field of view for these images is 205 pm. glial fibrillary acidic protein (GFAP) and vimentin contain both unique and overlapping phosphorylation sites for both PKA and PKC (Harrison and Mobley, 1991), indicating that these cytoskeletal components may be important to the stellation response. However, GFAP may not be crucial to the stellation response since stellation occurs in LRM55 glioma cells (Shain et al, 1987), which do not express appreciable amounts of GFAP (Shain et al, unpublished observations).…”
Section: Introductionmentioning
confidence: 99%
“…No phosphorylation was observed in the C-terminal fragment (1 5 kDa). In other studies in which GFAP was phosphorylated in intact cells, purified, and then cleaved with NTCB, only one band at 35 kDa was observed (Hamson and Mobley, 1991). It Tryptic peptide maps of GFAP (Fig.…”
Section: Fig 3 Tryptic Phosphopeptide Maps Of Gfap Phosphorylated Bmentioning
confidence: 85%